2020
DOI: 10.1080/1744666x.2021.1833720
|View full text |Cite
|
Sign up to set email alerts
|

Local Bacteriotherapy – a promising preventive tool in recurrent respiratory infections

Abstract: Introduction: Children with recurrent respiratory infections (RRI) represent a social issue for the economic burden and the negative family impact. Local Bacteriotherapy is an attractive therapeutic strategy that could be potentially effective in preventing infections. The current article remarks on the existing evidence of preventing RRI by Local Bacteriotherapy. Areas covered: The literature search methodology was based on the articles cited by PubMed from 1980 to 2020. Respiratory infections include rhino-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Confirmatory observations came from other bacterial species such as Streptococcus oralis 89a administered as an oral spray. Despite being interesting, the studies showed some methodological limitations and missed microbiological findings [77].…”
Section: Microbial-derived Products As Possible Interventions In Pedimentioning
confidence: 99%
“…Confirmatory observations came from other bacterial species such as Streptococcus oralis 89a administered as an oral spray. Despite being interesting, the studies showed some methodological limitations and missed microbiological findings [77].…”
Section: Microbial-derived Products As Possible Interventions In Pedimentioning
confidence: 99%
“…Recurrent RTIs (RRTIs), defined as eight or more documented RTIs per year up to 3 years of age and six or more episodes in children older than 3 years, are also a very common clinical condition in pediatric age with an important social and economic impact [ 5 , 6 , 7 , 8 ]. In Italy, it is estimated that approximately 25% of children under 1 year of age and 6% of children during the first 6 years of life experience RRTIs, making them one of the main reasons for patient referral during the first years of life [ 6 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is important to focus on alternative strategies to prevent and treat infection in order to reduce antibiotic use and the incidence of drug resistance [ 8 ]. Local bacteriotherapy has been proposed as a potential strategy, based on the administration of oral probiotics that can exert beneficial effects to maintain and/or restore healthy microbial communities within the URT and reduce the severity, duration, and incidence of re-infection, interfering with the adhesion and colonization of potential pathogens by the production of antimicrobial peptides (bacteriocins) and immunomodulatory mediators; likewise, competitive adherence and co-aggregation between pathogens and probiotic strains can enhance the antagonistic activity of probiotics [ 9 ].…”
Section: Introductionmentioning
confidence: 99%